Model Pembelajaran Amtsal Dan Implikasinya Dalam Pembelajaran Pendidikan Agama Islam - Haryati, Tati; Syahidin, Syahidin; Suresman, Edi (ZAD Al-Mufassirin, 2023)
Quranic verses contain amtsal (examples and figurative language) which can be used in teaching. As a learning model, amtsal can become a necessary alternative to achieve efficient and effective teaching and learning. Yet, this model in teaching is not sufficiently explored. A review of Quranic verses identifies three types of amtsal; musharrah, kaminah, and mursalah. Literature review shows that this model enables teachers to present abstract perceptions as sensed information and knowledge. It allows students to understand and grasp the meaning of abstract concepts easily and receive their hidden meanings which can become useful guidelines in life. The study concludes that this Quran-based model is effective to be used in Islamic Religious Education as it supports students’ critical thinking and increases their acceptance of Islamic teachings. The model also makes learning more fun and engaging.